2022
DOI: 10.3390/plants11192473
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Heat-Tolerance Screening and Genetic Diversity of Pea (Pisum sativum L.) Germplasms

Abstract: Pea (Pisum sativum L.) is an important legume crop. However, the yield of pea is adversely affected by heat stress in China. In this study, heat-tolerant germplasms were screened and evaluated in the field under multi-conditions. The results showed that heat stress could significantly affect pea yield. On the basis of grain weight per plant, 257 heat-tolerant and 175 heat-sensitive accessions were obtained from the first year’s screening, and 26 extremely heat-tolerant and 19 extremely heat-sensitive accession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Furthermore, local pea land races have reported to carry many important traits for various biotic and abiotic stresses including HS and such races should be utilized in pea breeding program aimed to improve the HS tolerance (Bahuguna et al, 2015;Kilasi et al, 2018). In China, Wang et al (2022) screened 2358 worldwide pea accessions for three years and identified 26 extremely heat tolerant accessions. These accessions can be used for breeding for HS tolerance in pea.…”
Section: Harnessing Crop Germplasm Repertoirementioning
confidence: 99%
“…Furthermore, local pea land races have reported to carry many important traits for various biotic and abiotic stresses including HS and such races should be utilized in pea breeding program aimed to improve the HS tolerance (Bahuguna et al, 2015;Kilasi et al, 2018). In China, Wang et al (2022) screened 2358 worldwide pea accessions for three years and identified 26 extremely heat tolerant accessions. These accessions can be used for breeding for HS tolerance in pea.…”
Section: Harnessing Crop Germplasm Repertoirementioning
confidence: 99%
“…Salt stress has direct impacts on photosynthesis, such as diffusion restrictions via the stomata and mesophyll cells, which change the photosynthetic metabolism [8,9]. High levels of Na + uptake by the cytoplasm decrease metabolic and various enzymes' activities and also inhibit the photosynthesis process at the cellular level [9,10]. The effects of salinity on photosynthesis may include a reduction in electron transfer, the inactivation of the photosystem II reaction centers, the destruction of the oxygen-evolving complex, and a reduction in the donor side's ability to transfer electrons [11,12].…”
Section: Introductionmentioning
confidence: 99%